A high-voltage resistant porcelain insulator and a preparation method thereof

CN122958155APending Publication Date: 2026-10-23PINGXIANG JINHONG PORCELAIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611010599.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

这些环境应力可能导致瓷体表面出现微裂纹、釉层老化剥落,或使瓷材料的机械强度逐步衰减,最终引发绝缘子脆断等事故

Benefits of technology

[0013]本发明的有益效果在于:采用本发明所述方法制备的瓷绝缘子具有良好的击穿耐受性能和耐候性能,表现为较高的击穿电压,且经过高低温反复作用后不发生损坏,提高了瓷绝缘子的耐用性。本发明通过添加制备的改性氧化铝-多孔二氧化硅复合粉末,能够进一步地提高氧化铝基瓷绝缘子的性能。其原因可能在于:本发明首先通过模板剂法制备了碳掺杂的介孔二氧化硅,通过添加聚乙二醇辛基苯基醚引入碳点,降低原料的介电常数,使得在电场作用下产生的极化电荷较少,从而提高击穿电压值。另外,通过添加聚乙二醇辛基苯基醚有利于提高介孔二氧化硅的分散性,减少团聚。另一方面,由于瓷的电击穿通道大部分是在晶界处,因此本发明通过负载ZnO-ZnS复合物,能够有效地细化陶瓷的晶粒尺寸,晶粒越细小,单位体积内的晶界越多,有效地阻碍击穿裂纹的扩展路径,提高击穿电压;且ZnO-ZnS复合物能够显著减少相界面的孔隙率,提高致密度。最后,通过钇氧化物在相界面区形成低熔点的液相,有助于陶瓷颗粒间的物质重新分布和填充孔隙,进一步提高致密度,从而提高陶瓷的击穿耐受性能和耐候性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1783482805767-000001
    Figure REF-OBJ-1783482805767-000001
Patent Text Reader

Abstract

The application discloses a high-pressure-resistant porcelain insulator, raw materials of which comprise modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium sesquioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder and zirconium dioxide powder. The porcelain insulator prepared by the method has good breakdown resistance and weather resistance, shows a high breakdown voltage, and is not damaged after repeated high and low temperature actions, thereby improving the durability of the porcelain insulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special ceramic product manufacturing technology, and in particular to a high-voltage resistant porcelain insulator and its preparation method. Background Technology

[0002] Porcelain insulators, with their excellent mechanical strength, electrical insulation properties, and good chemical stability, have long been widely used in high-voltage and ultra-high-voltage transmission lines, serving as one of the key pieces of equipment for ensuring the safe and stable operation of power systems. However, with the continuous expansion of power grids, the increasing voltage levels of transmission lines, and the growing complexity of the service environment for power equipment, porcelain insulators operating in outdoor natural environments face increasingly severe challenges.

[0003] The external insulation performance of porcelain insulators, especially their high breakdown withstand voltage characteristics, is a core indicator determining their operational reliability. Breakdown typically occurs within the insulator. When the electric field strength acting on the porcelain body exceeds the material's own breakdown field strength, the insulator will undergo irreversible destructive discharge, directly leading to equipment failure or even causing large-scale power outages. In actual operation, microstructural defects within porcelain insulators, such as pores, microcracks, grain boundary impurities, and residual stress concentration areas formed during sintering, can easily induce local electric field distortion under the continuous or transient impacts of long-term operating voltage, switching overvoltage, and lightning overvoltage, leading to partial discharge and gradually developing into a penetrating breakdown path. Especially in ultra-high voltage and direct current transmission systems, even more stringent requirements are placed on the volume resistivity, dielectric strength, and microstructural compactness of the material. On the other hand, the weather resistance of porcelain insulators also directly affects their long-term service life. Outdoor porcelain insulators are subjected to the combined effects of various environmental factors such as drastic temperature changes, freeze-thaw cycles, acid rain erosion, and wind and sand abrasion year-round. These environmental stresses can lead to microcracks on the surface of the porcelain insulator, glaze aging and peeling, or a gradual decrease in the mechanical strength of the porcelain material, ultimately causing accidents such as brittle fracture of the insulator. However, existing porcelain insulator products still have significant shortcomings in simultaneously improving flashover voltage and weather resistance. Therefore, developing a new type of porcelain insulator that combines high flashover voltage and excellent weather resistance is of great practical significance and application value for improving the operational safety and reliability of transmission lines in complex environments. Summary of the Invention

[0004] Therefore, this invention provides a high-voltage resistant porcelain insulator, the raw materials of which include: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) Polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water in a reaction vessel and stirred evenly. Then hydrochloric acid was added. After the addition was completed, the mixture was heated in a water bath and stirred to obtain a mixed liquid. Then, tetraethyl orthosilicate was added to the mixed liquid under the condition of water bath heat preservation. After the addition was completed, the mixture was heated in a water bath and stirred. Then the reaction vessel was sealed and heated to above 120°C for hydrothermal treatment. After the treatment was completed, the mixture was cooled to room temperature, the solid and liquid were separated, and the solid phase was calcined to obtain silica matrix powder. (2) The sieved alumina powder and the silica matrix powder are mixed evenly to obtain a mixed powder; ethanolamine and zinc acetate dihydrate are added to ethanol, heated in a water bath and stirred, and refluxed during the heating process; after stirring, the mixture is allowed to stand and age to obtain a precursor liquid, the mixed powder is added to the precursor liquid, and the mixture is placed under negative pressure for pressure treatment. After pressure treatment, solid-liquid separation is performed, the solid phase is dried, and after drying, the mixture is immersed in the precursor liquid again, pressure treatment is performed under negative pressure, solid-liquid separation is performed again, and the solid phase is dried. The above steps of immersion, negative pressure, solid-liquid separation, and drying are repeated until the required loading is reached, and then calcined to obtain a loaded powder; the loaded powder is added to an aqueous solution of zinc acetate in a reactor, ammonia is added to adjust the pH of the solution to weak alkalinity, thiourea is added, and then the mixture is stirred evenly. The reactor is sealed and subjected to hydrothermal treatment. After treatment, the mixture is cooled to room temperature, solid-liquid separation is performed, the solid phase is washed, and dried to obtain a modified powder; (3) Prepare an aqueous solution of yttrium nitrate, add the modified powder to the aqueous solution of yttrium nitrate, stir evenly, add ammonia water, stir to react after the addition is complete, then separate the solid and liquid, wash the solid phase, dry, and calcine to obtain the modified alumina-porous silica composite powder.

[0005] Further, the raw materials, by weight, are: 50 parts of modified alumina-porous silica composite powder, 10-15 parts of potassium feldspar powder, 20-30 parts of kaolin, 8-10 parts of chromium trioxide powder, 8-10 parts of magnesium oxide powder, 2-5 parts of titanium dioxide powder, 1-5 parts of silicon carbide powder, and 1-5 parts of zirconium dioxide powder; wherein the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are all sieved powders that have passed through a 300-mesh sieve.

[0006] Further, in step (1), the ratio of the amount of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water to the amount of hydrochloric acid and tetraethyl orthosilicate added is polyethylene glycol octylphenyl ether: hexadecyltrimethylammonium bromide: deionized water: hydrochloric acid: tetraethyl orthosilicate = 1.5-1.8g: 0.1-0.3g: 80g: 20g: 5-7g; wherein the mass percentage of the solute in the hydrochloric acid is 5%-6%.

[0007] Further, in step (1), the mixture is heated to 40°C in a water bath and kept warm; the hydrothermal treatment lasts for 8 to 10 hours; the calcination temperature is 280 to 300°C and the calcination time is 1 to 2 hours.

[0008] Further, in step (2), the mass ratio of the sieved alumina powder to the silica matrix powder is 40:10; the ratio of ethanolamine to zinc acetate dihydrate added to ethanol is 0.4-0.6g:1-2g:100mL; and the loaded powder is obtained by calcination at 350-370℃ for 4-5 hours.

[0009] Further, in step (2), the concentration of zinc acetate in the aqueous solution is 8-10 g / 100 mL, and the solvent is water; the ratio of the loaded powder to the aqueous solution of zinc acetate is 1 g of loaded powder to 30-50 mL of aqueous solution of zinc acetate, the pH of the solution is adjusted to 10 with ammonia, and the ratio of the amount of thiourea added to the amount of loaded powder is 1 g of loaded powder to 1.6-1.8 g of thiourea; the hydrothermal treatment temperature is 170-180°C, and the treatment time is 15-20 h.

[0010] Further, in step (3), the concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 50-60 g / L, and the solvent is water; the ratio of the modified powder added to the aqueous solution of yttrium nitrate is modified powder: aqueous solution of yttrium nitrate = 1 g: 30-40 mL, ammonia water is added to adjust the pH of the solution to 11, and the mixture is stirred for more than 5 hours after the addition is completed; the calcination temperature is 400-450℃, and the calcination time is 2-3 hours.

[0011] The present invention also discloses a method for preparing the above-mentioned high-voltage resistant porcelain insulator, wherein the raw materials are mixed with water by ball milling to obtain a slurry; the slurry is then filtered, allowed to stand and age, and pressed into a blank in a mold; the blank is then dried and fired to form the high-voltage resistant porcelain insulator.

[0012] Furthermore, the firing temperature is 1500–1550°C.

[0013] The beneficial effects of this invention are as follows: the porcelain insulators prepared by the method described in this invention have good breakdown resistance and weather resistance, exhibiting a high breakdown voltage, and do not suffer damage after repeated exposure to high and low temperatures, thus improving the durability of the porcelain insulators. This invention further improves the performance of alumina-based porcelain insulators by adding the prepared modified alumina-porous silica composite powder. This may be because: this invention first prepares carbon-doped mesoporous silica using a template agent method, and introduces carbon dots by adding polyethylene glycol octylphenyl ether, reducing the dielectric constant of the raw material, resulting in less polarization charge generated under an electric field, thereby increasing the breakdown voltage. In addition, the addition of polyethylene glycol octylphenyl ether helps improve the dispersibility of the mesoporous silica and reduces agglomeration. On the other hand, since most of the electrical breakdown channels in ceramics are located at grain boundaries, this invention, by loading a ZnO-ZnS composite, can effectively refine the grain size of the ceramic. The finer the grains, the more grain boundaries per unit volume, effectively hindering the propagation path of breakdown cracks and increasing the breakdown voltage. Furthermore, the ZnO-ZnS composite can significantly reduce the porosity of the phase interface, increasing density. Finally, the formation of a low-melting-point liquid phase by yttrium oxide in the phase interface region facilitates the redistribution of material between ceramic particles and the filling of pores, further increasing density and thus improving the ceramic's breakdown resistance and weather resistance. Detailed Implementation

[0014] The present invention will be further described below with reference to the embodiments.

[0015] Example 1

[0016] A high-voltage resistant porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 10 parts potassium feldspar powder, 20 parts kaolin, 8 parts chromium trioxide powder, 8 parts magnesium oxide powder, 2 parts titanium dioxide powder, 1 part silicon carbide powder, and 1 part zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) In a reaction vessel, polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water and stirred for 30 minutes. Then, hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept at that temperature for 3 hours to obtain a homogeneous solution. Then, tetraethyl orthosilicate was added to the homogeneous solution while it was kept at 40°C in a water bath. The ratio of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water and the ratio of hydrochloric acid and tetraethyl orthosilicate added was 1.5g:0.1g:80g:20g:5g. The mass percentage of solute in the hydrochloric acid was 5%. After the addition, the mixture was kept at 40°C in a water bath and stirred for 5 hours. Then, the reaction vessel was sealed and heated to 120°C for hydrothermal treatment for 8 hours. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was calcined at 280°C for 2 hours to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.4g: 1g: 100mL; the mixture is heated to 70℃ in a water bath and stirred for 30min, with reflux during the heating process; after stirring, the mixture is allowed to stand and age for 15h to obtain a precursor liquid. The mixed powder is added to the precursor liquid to ensure that the mixed powder is fully soaked. The mixture is then placed under negative pressure (0.01 standard atmospheres) for 20min, followed by solid-liquid separation. The solid phase is dried at 100℃ for 30min, and then soaked again in the precursor liquid under negative pressure (0.01 standard atmospheres) for 20m. The solid phase was soaked, then separated into solid and liquid phases. The solid phase was dried at 100°C for 30 minutes. This process of soaking, negative pressure holding, solid-liquid separation, and drying was repeated six times. The solid phase was then calcined at 350°C for 5 hours to obtain the loaded powder. The loaded powder was then added to an aqueous solution of zinc acetate in a reactor. The concentration of zinc acetate in the aqueous solution was 8 g / 100 mL, and the solvent was water. The ratio of the loaded powder to the zinc acetate aqueous solution was 1 g:30 mL. Ammonia (25% solute by mass) was added to adjust the pH of the solution to 10. Thiourea was then added, with a ratio of 1 g:1.6 g of loaded powder to 1 g of thiourea. The mixture was stirred for 1 hour, the reactor was sealed, and hydrothermal treatment was performed at 170°C for 15 hours. After treatment, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 100°C for 2 hours to obtain the modified powder. (3) Prepare an aqueous solution of yttrium nitrate. Add the modified powder to the aqueous solution of yttrium nitrate. The concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 50 g / L, and the solvent is water. The ratio of the modified powder added to the aqueous solution of yttrium nitrate is 1 g: 30 mL. Stir for 20 min, then add ammonia water (25% solute by mass) to adjust the pH of the solution to 11. After the addition is completed, stir for 5 h, then separate the solid and liquid phases. Wash the solid phase three times with deionized water, dry at 100℃ for 2 h, and calcine at 400℃ for 3 h to obtain the modified alumina-porous silica composite powder.

[0017] The preparation method of the above-mentioned high-voltage resistant porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the high-voltage resistant porcelain insulator.

[0018] Example 2

[0019] A high-voltage resistant porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 10 parts potassium feldspar powder, 25 parts kaolin, 9 parts chromium trioxide powder, 9 parts magnesium oxide powder, 3 parts titanium dioxide powder, 2 parts silicon carbide powder, and 2 parts zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) In a reaction vessel, polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water and stirred for 30 minutes. Then, hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept at that temperature for 3 hours to obtain a homogeneous solution. Then, tetraethyl orthosilicate was added to the homogeneous solution while it was kept at 40°C in a water bath. The ratio of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water and the ratio of hydrochloric acid and tetraethyl orthosilicate added was 1.6g:0.2g:80g:20g:6g. The mass percentage of the solute in the hydrochloric acid was 5%. After the addition, the mixture was kept at 40°C in a water bath and stirred for 5 hours. Then, the reaction vessel was sealed and heated to 120°C for hydrothermal treatment for 8 hours. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was calcined at 280°C for 2 hours to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate added to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.5g: 1g: 100mL; the mixture is heated to 70℃ in a water bath and stirred for 30min, with reflux during the heating process; after stirring, the mixture is allowed to stand and age for 15h to obtain a precursor liquid. The mixed powder is added to the precursor liquid to ensure that the mixed powder is fully soaked. The mixture is then placed under negative pressure (0.01 standard atmospheres) for 20min. After pressure holding, the solid and liquid phases are separated, and the solid phase is dried at 100℃ for 30min. After drying, the mixture is soaked again in the precursor liquid and pressure-treated under negative pressure (0.01 standard atmospheres) for 20m. The solid phase was soaked, then separated into solid and liquid phases. The solid phase was dried at 100°C for 30 minutes. This process of soaking, negative pressure holding, solid-liquid separation, and drying was repeated six times. The solid phase was then calcined at 350°C for 5 hours to obtain the loaded powder. The loaded powder was then added to an aqueous solution of zinc acetate in a reactor. The concentration of zinc acetate in the aqueous solution was 9 g / 100 mL, and the solvent was water. The ratio of the loaded powder to the zinc acetate aqueous solution was 1 g:30 mL. Ammonia (25% solute by mass) was added to adjust the pH of the solution to 10. Thiourea was then added, with a ratio of 1 g:1.7 g of loaded powder to 1 g of thiourea. The mixture was stirred for 1 hour, the reactor was sealed, and hydrothermal treatment was performed at 170°C for 15 hours. After treatment, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 100°C for 2 hours to obtain the modified powder. (3) Prepare an aqueous solution of yttrium nitrate. Add the modified powder to the aqueous solution of yttrium nitrate. The concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 55 g / L, and the solvent is water. The ratio of the modified powder added to the aqueous solution of yttrium nitrate is 1 g: 30 mL. Stir for 20 min, then add ammonia water (25% solute by mass) to adjust the pH of the solution to 11. After the addition is completed, stir for 5 h, then separate the solid and liquid phases. Wash the solid phase three times with deionized water, dry at 100℃ for 2 h, and calcine at 400℃ for 3 h to obtain the modified alumina-porous silica composite powder.

[0020] The preparation method of the above-mentioned high-voltage resistant porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the high-voltage resistant porcelain insulator.

[0021] Example 3

[0022] A high-voltage resistant porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 15 parts potassium feldspar powder, 25 parts kaolin, 9 parts chromium trioxide powder, 9 parts magnesium oxide powder, 4 parts titanium dioxide powder, 4 parts silicon carbide powder, and 4 parts zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) In a reaction vessel, polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water and stirred for 30 minutes. Then, hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept at that temperature for 3 hours to obtain a homogeneous solution. Then, tetraethyl orthosilicate was added to the homogeneous solution while it was kept at 40°C in a water bath. The ratio of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water and the ratio of hydrochloric acid and tetraethyl orthosilicate added was 1.7g:0.2g:80g:20g:6g. The mass percentage of solute in the hydrochloric acid was 6%. After the addition, the mixture was kept at 40°C in a water bath and stirred for 5 hours. Then, the reaction vessel was sealed and heated to 120°C for hydrothermal treatment for 8 hours. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was calcined at 300°C for 1 hour to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate added to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.5g: 2g: 100mL; the mixture is heated to 70℃ in a water bath and stirred for 30min, with reflux during the heating process; after stirring, the mixture is allowed to stand and age for 15h to obtain a precursor liquid. The mixed powder is added to the precursor liquid to ensure that the mixed powder is fully soaked. The mixture is then placed under negative pressure (0.01 standard atmospheres) for 20min, followed by solid-liquid separation. The solid phase is dried at 100℃ for 30min, and then soaked again in the precursor liquid under negative pressure (0.01 standard atmospheres) for 20m. The solid phase was soaked, then separated into solid and liquid phases. The solid phase was dried at 100°C for 30 minutes. This process of soaking, negative pressure holding, solid-liquid separation, and drying was repeated six times. The solid phase was then calcined at 370°C for 4 hours to obtain the loaded powder. The loaded powder was then added to an aqueous solution of zinc acetate in a reactor. The concentration of zinc acetate in the aqueous solution was 9 g / 100 mL, and the solvent was water. The ratio of the loaded powder to the zinc acetate aqueous solution was 1 g:30 mL. Ammonia (25% solute by mass) was added to adjust the pH of the solution to 10. Thiourea was then added, with a ratio of 1 g:1.7 g of loaded powder to 1 g of thiourea. The mixture was stirred for 1 hour, the reactor was sealed, and hydrothermal treatment was performed at 180°C for 15 hours. After treatment, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 100°C for 2 hours to obtain the modified powder. (3) Prepare an aqueous solution of yttrium nitrate. Add the modified powder to the aqueous solution of yttrium nitrate. The concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 55 g / L, and the solvent is water. The ratio of the modified powder added to the aqueous solution of yttrium nitrate is 1 g: 30 mL. Stir for 20 min, then add ammonia water (25% solute by mass) to adjust the pH of the solution to 11. After the addition is completed, stir for 5 h, then separate the solid and liquid phases. Wash the solid phase three times with deionized water, dry at 100℃ for 2 h, and calcine at 450℃ for 2 h to obtain the modified alumina-porous silica composite powder.

[0023] The preparation method of the above-mentioned high-voltage resistant porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the high-voltage resistant porcelain insulator.

[0024] Example 4

[0025] A high-voltage resistant porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 15 parts potassium feldspar powder, 30 parts kaolin, 10 parts chromium trioxide powder, 10 parts magnesium oxide powder, 5 parts titanium dioxide powder, 5 parts silicon carbide powder, and 5 parts zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) In a reaction vessel, polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water and stirred for 30 minutes. Then, hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept at that temperature for 3 hours to obtain a homogeneous solution. Then, tetraethyl orthosilicate was added to the mixture while it was kept at 40°C in a water bath. The ratio of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water and the ratio of hydrochloric acid and tetraethyl orthosilicate added was 1.8g:0.3g:80g:20g:7g. The mass percentage of the solute in the hydrochloric acid was 6%. After the addition, the mixture was kept at 40°C in a water bath and stirred for 5 hours. Then, the reaction vessel was sealed and heated to 120°C for hydrothermal treatment for 8 hours. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was calcined at 300°C for 1 hour to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate added to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.6g: 2g: 100mL; the mixture is heated to 70℃ in a water bath and stirred for 30min, with reflux during the heating process; after stirring, the mixture is allowed to stand and age for 15h to obtain a precursor liquid. The mixed powder is added to the precursor liquid to ensure that the mixed powder is fully soaked. The mixture is then placed under negative pressure (0.01 standard atmospheres) for 20min. After pressure holding, the solid and liquid phases are separated, and the solid phase is dried at 100℃ for 30min. After drying, the mixture is soaked again in the precursor liquid and pressure-treated under negative pressure (0.01 standard atmospheres) for 20min. n. Then, perform solid-liquid separation, dry the solid phase at 100℃ for 30 min, and repeat the above soaking, negative pressure holding, solid-liquid separation, and drying steps a total of 6 times. Then, calcine at 370℃ for 4 h to obtain the loaded powder. In a reactor, add the loaded powder to an aqueous solution of zinc acetate, where the concentration of zinc acetate is 10 g / 100 mL and the solvent is water. The ratio of the loaded powder to the zinc acetate aqueous solution is 1 g: 30 mL. Add ammonia water (solute mass percentage 25%) to adjust the pH of the solution to 10, then add thiourea, where the ratio of thiourea to the loaded powder is 1 g: 1.8 g. Stir for 1 h, seal the reactor, and perform hydrothermal treatment at 180℃ for 15 h. After treatment, cool to room temperature, perform solid-liquid separation, wash the solid phase three times with deionized water, and dry at 100℃ for 2 h to obtain the modified powder. (3) Prepare an aqueous solution of yttrium nitrate. Add the modified powder to the aqueous solution of yttrium nitrate. The concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 60 g / L, and the solvent is water. The ratio of the modified powder added to the aqueous solution of yttrium nitrate is 1 g: 30 mL. Stir for 20 min, then add ammonia water (25% solute by mass) to adjust the pH of the solution to 11. After the addition is completed, stir for 5 h, then separate the solid and liquid phases. Wash the solid phase three times with deionized water, dry at 100 °C for 2 h, and calcine at 450 °C for 2 h to obtain the modified alumina-porous silica composite powder.

[0026] The preparation method of the above-mentioned high-voltage resistant porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the high-voltage resistant porcelain insulator.

[0027] Comparative Example 1 A comparative porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 15 parts potassium feldspar powder, 25 parts kaolin, 9 parts chromium trioxide powder, 9 parts magnesium oxide powder, 4 parts titanium dioxide powder, 4 parts silicon carbide powder, and 4 parts zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) Hexadecyltrimethylammonium bromide was added to deionized water in a reactor and stirred for 30 min. Then hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept warm for 3 h to obtain a mixed solution. Then, tetraethyl orthosilicate was added to the mixed solution while it was kept warm in a water bath at 40°C. The ratio of the amount of hexadecyltrimethylammonium bromide added to deionized water to the amount of hydrochloric acid and tetraethyl orthosilicate added was hexadecyltrimethylammonium bromide:deionized water:hydrochloric acid:tetraethyl orthosilicate = 0.2 g:80 g:20 g:6 g. The mass percentage of the solute in the hydrochloric acid was 6%. After the addition, the mixture was kept warm in a water bath at 40°C for 5 h and then the reactor was sealed. The mixture was heated to 120°C and hydrothermally treated for 8 h. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid were separated. The solid phase was calcined at 300°C for 1 h to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate added to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.5g: 2g: 100mL; the mixture is heated to 70℃ in a water bath and stirred for 30min, with reflux during the heating process; after stirring, the mixture is allowed to stand and age for 15h to obtain a precursor liquid. The mixed powder is added to the precursor liquid to ensure that the mixed powder is fully soaked. The mixture is then placed under negative pressure (0.01 standard atmospheres) for 20min, followed by solid-liquid separation. The solid phase is dried at 100℃ for 30min, and then soaked again in the precursor liquid under negative pressure (0.01 standard atmospheres) for 20m. The solid phase was soaked, then separated into solid and liquid phases. The solid phase was dried at 100°C for 30 minutes. This process of soaking, negative pressure holding, solid-liquid separation, and drying was repeated six times. The solid phase was then calcined at 370°C for 4 hours to obtain the loaded powder. The loaded powder was then added to an aqueous solution of zinc acetate in a reactor. The concentration of zinc acetate in the aqueous solution was 9 g / 100 mL, and the solvent was water. The ratio of the loaded powder to the zinc acetate aqueous solution was 1 g:30 mL. Ammonia (25% solute by mass) was added to adjust the pH of the solution to 10. Thiourea was then added, with a ratio of 1 g:1.7 g of loaded powder to 1 g of thiourea. The mixture was stirred for 1 hour, the reactor was sealed, and hydrothermal treatment was performed at 180°C for 15 hours. After treatment, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 100°C for 2 hours to obtain the modified powder. (3) Prepare an aqueous solution of yttrium nitrate. Add the modified powder to the aqueous solution of yttrium nitrate. The concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 55 g / L, and the solvent is water. The ratio of the modified powder added to the aqueous solution of yttrium nitrate is 1 g: 30 mL. Stir for 20 min, then add ammonia water (25% solute by mass) to adjust the pH of the solution to 11. After the addition is completed, stir for 5 h, then separate the solid and liquid phases. Wash the solid phase three times with deionized water, dry at 100℃ for 2 h, and calcine at 450℃ for 2 h to obtain the modified alumina-porous silica composite powder.

[0028] The preparation method of the above-mentioned porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the porcelain insulator described in this comparative example.

[0029] Comparative Example 2 A comparative porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 15 parts potassium feldspar powder, 25 parts kaolin, 9 parts chromium trioxide powder, 9 parts magnesium oxide powder, 4 parts titanium dioxide powder, 4 parts silicon carbide powder, and 4 parts zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) In a reaction vessel, polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water and stirred for 30 minutes. Then, hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept at that temperature for 3 hours to obtain a homogeneous solution. Then, tetraethyl orthosilicate was added to the homogeneous solution while it was kept at 40°C in a water bath. The ratio of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water and the ratio of hydrochloric acid and tetraethyl orthosilicate added was 1.7g:0.2g:80g:20g:6g. The mass percentage of solute in the hydrochloric acid was 6%. After the addition, the mixture was kept at 40°C in a water bath and stirred for 5 hours. Then, the reaction vessel was sealed and heated to 120°C for hydrothermal treatment for 8 hours. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was calcined at 300°C for 1 hour to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.5g: 2g: 100mL; the mixture is heated in a water bath to 70℃ and stirred for 30min, with reflux during the heating process; after stirring, the mixture is allowed to stand and age for 15h. A precursor fluid was obtained, and the mixed powder was added to the precursor fluid to fully soak the mixed powder. The mixture was then placed under negative pressure (0.01 standard atmospheres) for 20 minutes. After pressure holding, solid-liquid separation was performed, and the solid phase was dried at 100°C for 30 minutes. After drying, the mixture was soaked in the precursor fluid again and pressure-held under negative pressure (0.01 standard atmospheres) for 20 minutes. Solid-liquid separation was performed again, and the solid phase was dried at 100°C for 30 minutes. The above soaking, negative pressure holding, solid-liquid separation, and drying steps were repeated a total of 6 times. Finally, the mixture was calcined at 370°C for 4 hours to obtain the loaded powder. (3) Prepare an aqueous solution of yttrium nitrate. Add the loaded powder to the aqueous solution of yttrium nitrate. The concentration of yttrium nitrate in the aqueous solution of yttrium nitrate is 55 g / L, and the solvent is water. The ratio of the loaded powder to the aqueous solution of yttrium nitrate is 1 g: 30 mL. Stir for 20 min, then add ammonia water (25% solute by mass) to adjust the pH of the solution to 11. After the addition is completed, stir for 5 h, then separate the solid and liquid phases. Wash the solid phase three times with deionized water, dry at 100 °C for 2 h, and calcine at 450 °C for 2 h to obtain the modified alumina-porous silica composite powder.

[0030] The preparation method of the above-mentioned porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the porcelain insulator described in this comparative example.

[0031] Comparative Example 3 A comparative porcelain insulator comprises the following raw materials: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The raw materials, by weight, are: 50 parts modified alumina-porous silica composite powder, 15 parts potassium feldspar powder, 25 parts kaolin, 9 parts chromium trioxide powder, 9 parts magnesium oxide powder, 4 parts titanium dioxide powder, 4 parts silicon carbide powder, and 4 parts zirconium dioxide powder. All the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are sieved through a 300-mesh sieve. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) In a reaction vessel, polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water and stirred for 30 minutes. Then, hydrochloric acid was added. After the addition was completed, the mixture was heated to 40°C in a water bath and kept at that temperature for 3 hours to obtain a homogeneous solution. Then, tetraethyl orthosilicate was added to the homogeneous solution while it was kept at 40°C in a water bath. The ratio of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water and the ratio of hydrochloric acid and tetraethyl orthosilicate added was 1.7g:0.2g:80g:20g:6g. The mass percentage of solute in the hydrochloric acid was 6%. After the addition, the mixture was kept at 40°C in a water bath and stirred for 5 hours. Then, the reaction vessel was sealed and heated to 120°C for hydrothermal treatment for 8 hours. After the treatment was completed, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was calcined at 300°C for 1 hour to obtain silica matrix powder. (2) The sieved alumina powder (passed through a 300-mesh sieve) and the silica matrix powder are mixed evenly to obtain a mixed powder; the mass ratio of the sieved alumina powder to the silica matrix powder is sieved alumina powder: silica matrix powder = 40:10; ethanolamine and zinc acetate dihydrate are added to ethanol, and the mass ratio of ethanolamine to zinc acetate dihydrate to ethanol is ethanolamine: zinc acetate dihydrate: ethanol = 0.5g: 2g: 100mL; the mixture is heated in a water bath to 70℃ and stirred for 3 minutes. 0 min, condensation and reflux during heat preservation; after stirring, let stand and age for 15 h to obtain precursor liquid, add the mixed powder to the precursor liquid to fully soak the mixed powder, place under negative pressure (0.01 standard atmospheres) for 20 min, then separate solid and liquid, dry the solid phase at 100℃ for 30 min, after drying, soak again in the precursor liquid, hold under negative pressure (0.01 standard atmospheres) for 20 min, then separate solid and liquid again, the solid phase 10 The mixture was dried at 0℃ for 30 minutes. The soaking, negative pressure holding, solid-liquid separation, and drying steps were repeated six times. The mixture was then calcined at 370℃ for 4 hours to obtain the loaded powder. The loaded powder was then added to an aqueous solution of zinc acetate in a reaction vessel. The concentration of zinc acetate in the aqueous solution was 9 g / 100 mL, and the solvent was water. The ratio of the loaded powder to the aqueous solution of zinc acetate was 1 g: 30 mL. Ammonia water (25% by mass) was added. Adjust the pH of the solution to 10, then add thiourea. The ratio of the amount of thiourea added to the amount of the loaded powder is 1 g: 1.7 g. Stir for 1 hour, seal the reactor, and perform hydrothermal treatment at 180°C for 15 hours. After treatment, cool to room temperature, separate the solid and liquid phases, wash the solid phase three times with deionized water, and dry it at 100°C for 2 hours to obtain the modified powder, which is the modified alumina-porous silica composite powder of this comparative example.

[0032] The preparation method of the above-mentioned porcelain insulator is as follows: the raw materials are mixed with water by ball milling to obtain a slurry. The ratio of raw material to ball to water is 1:1:1.2. The ball milling time is 8 hours and the rotation speed is 120 r / min. The slurry is filtered to obtain a water content of 23 wt%. It is then allowed to stand for aging for 15 hours and pressed into a blank in a mold. The blank is dried at 150°C for 1 hour and then fired at 1530°C for 90 minutes. It is then cooled to room temperature in the furnace to form the porcelain insulator described in this comparative example.

[0033] Example 5

[0034] The breakdown voltage of the porcelain insulators prepared by the methods described in the above embodiments and comparative examples was tested respectively. In addition, the porcelain insulators prepared by the methods described in the above embodiments and comparative examples were subjected to repeated freeze-thaw cycles at -50 to 40°C for 30 times, and the surface cracks were observed. The results are shown in Table 1.

[0035] As shown in Table 1, the porcelain insulators prepared using the method described in this invention exhibit good breakdown withstand performance and weather resistance, demonstrating a high breakdown voltage. Furthermore, they remain undamaged after repeated exposure to high and low temperatures, thus improving the durability of the porcelain insulators. Comparative examples and comparative cases show that this invention, by adding the prepared modified alumina-porous silica composite powder, can further improve the performance of alumina-based porcelain insulators. This may be because: this invention first prepares carbon-doped mesoporous silica using a template agent method, and then introduces carbon dots by adding polyethylene glycol octylphenyl ether, reducing the dielectric constant of the raw material and resulting in less polarization charge generated under an electric field, thereby increasing the breakdown voltage. Additionally, the addition of polyethylene glycol octylphenyl ether helps improve the dispersibility of the mesoporous silica and reduces agglomeration. On the other hand, since most of the electrical breakdown channels in ceramics are located at grain boundaries, this invention, by loading a ZnO-ZnS composite, can effectively refine the grain size of the ceramic. The finer the grains, the more grain boundaries per unit volume, effectively hindering the propagation path of breakdown cracks and increasing the breakdown voltage. Furthermore, the ZnO-ZnS composite can significantly reduce the porosity of the phase interface, increasing density. Finally, the formation of a low-melting-point liquid phase by yttrium oxide in the phase interface region facilitates the redistribution of material between ceramic particles and the filling of pores, further increasing density and thus improving the ceramic's breakdown resistance and weather resistance.

[0036] Table 1

[0037] The technical solutions provided by the present invention have been described in detail above. For those skilled in the art, there will be changes in specific implementation methods and application scope based on the ideas of the embodiments of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A high-voltage resistant porcelain insulator, characterized in that, The raw materials include: modified alumina-porous silica composite powder, potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder. The preparation method of the modified alumina-porous silica composite powder is as follows: (1) Polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide were added to deionized water in a reaction vessel and stirred evenly. Then hydrochloric acid was added. After the addition was completed, the mixture was heated in a water bath and stirred to obtain a mixed liquid. Then, tetraethyl orthosilicate was added to the mixed liquid under the condition of water bath heat preservation. After the addition was completed, the mixture was heated in a water bath and stirred. Then the reaction vessel was sealed and heated to above 120°C for hydrothermal treatment. After the treatment was completed, the mixture was cooled to room temperature, the solid and liquid were separated, and the solid phase was calcined to obtain silica matrix powder. (2) The sieved alumina powder and the silica matrix powder are mixed evenly to obtain a mixed powder; ethanolamine and zinc acetate dihydrate are added to ethanol, heated in a water bath and stirred, and refluxed during the heating process; after stirring, the mixture is allowed to stand and age to obtain a precursor liquid, the mixed powder is added to the precursor liquid, and the mixture is placed under negative pressure for pressure treatment. After pressure treatment, solid-liquid separation is performed, the solid phase is dried, and after drying, the mixture is immersed in the precursor liquid again, pressure treatment is performed under negative pressure, solid-liquid separation is performed again, and the solid phase is dried. The above steps of immersion, negative pressure, solid-liquid separation, and drying are repeated until the required loading is reached, and then calcined to obtain a loaded powder; the loaded powder is added to an aqueous solution of zinc acetate in a reactor, ammonia is added to adjust the pH of the solution to weak alkalinity, thiourea is added, and then the mixture is stirred evenly. The reactor is sealed and subjected to hydrothermal treatment. After treatment, the mixture is cooled to room temperature, solid-liquid separation is performed, the solid phase is washed, and dried to obtain a modified powder; (3) Prepare an aqueous solution of yttrium nitrate, add the modified powder to the aqueous solution of yttrium nitrate, stir evenly, add ammonia water, stir to react after the addition is complete, then separate the solid and liquid, wash the solid phase, dry, and calcine to obtain the modified alumina-porous silica composite powder.

2. The high-voltage resistant porcelain insulator according to claim 1, characterized in that, The raw materials, by weight, are as follows: 50 parts modified alumina-porous silica composite powder, 10-15 parts potassium feldspar powder, 20-30 parts kaolin, 8-10 parts chromium trioxide powder, 8-10 parts magnesium oxide powder, 2-5 parts titanium dioxide powder, 1-5 parts silicon carbide powder, and 1-5 parts zirconium dioxide powder; wherein the potassium feldspar powder, kaolin, chromium trioxide powder, magnesium oxide powder, titanium dioxide powder, silicon carbide powder, and zirconium dioxide powder are all sieved powders that have passed through a 300-mesh sieve.

3. A high-voltage resistant porcelain insulator according to claim 1, characterized in that, In step (1), the ratio of the amount of polyethylene glycol octylphenyl ether and hexadecyltrimethylammonium bromide added to deionized water to the amount of hydrochloric acid and tetraethyl orthosilicate added is polyethylene glycol octylphenyl ether: hexadecyltrimethylammonium bromide: deionized water: hydrochloric acid: tetraethyl orthosilicate = 1.5-1.8g: 0.1-0.3g: 80g: 20g: 5-7g; wherein the mass percentage of the solute in the hydrochloric acid is 5%-6%.

4. A high-voltage resistant porcelain insulator according to claim 1, characterized in that, In step (1), the mixture is heated to 40°C in a water bath and kept warm; the hydrothermal treatment lasts for 8 to 10 hours; the calcination temperature is 280 to 300°C and the calcination time is 1 to 2 hours.

5. A high-voltage resistant porcelain insulator according to claim 1, characterized in that, In step (2), the mass ratio of the sieved alumina powder to the silica matrix powder is 40:10; the ratio of ethanolamine to zinc acetate dihydrate added to ethanol is 0.4-0.6g:1-2g:100mL; and the loaded powder is obtained by calcination at 350-370℃ for 4-5 hours.

6. A high-voltage resistant porcelain insulator according to claim 1, characterized in that, In step (2), the concentration of zinc acetate in the aqueous solution is 8-10 g / 100 mL, and the solvent is water; the ratio of the loaded powder to the aqueous solution of zinc acetate is 1 g of loaded powder to 30-50 mL of aqueous solution of zinc acetate, the pH of the solution is adjusted to 10 with ammonia, and the ratio of the amount of thiourea added to the amount of loaded powder is 1 g of loaded powder to 1.6-1.8 g of thiourea; the hydrothermal treatment temperature is 170-180℃, and the treatment time is 15-20 h.

7. A high-voltage resistant porcelain insulator according to claim 1, characterized in that, In step (3), the concentration of yttrium nitrate in the aqueous solution is 50-60 g / L, and the solvent is water; the ratio of the modified powder added to the aqueous solution of yttrium nitrate is 1 g of modified powder to 30-40 mL of aqueous solution of yttrium nitrate, and ammonia water is added to adjust the pH of the solution to 11. After the addition is completed, the mixture is stirred for more than 5 hours; the calcination temperature is 400-450℃, and the calcination time is 2-3 hours.

8. The method for preparing a porcelain insulator according to any one of claims 2 to 7, characterized in that, The present invention also discloses a method for preparing the above-mentioned high-voltage resistant porcelain insulator, wherein the raw materials are mixed with water by ball milling to obtain a slurry; the slurry is then filtered, allowed to stand and age, and pressed into a blank in a mold; the blank is then dried and fired to form the high-voltage resistant porcelain insulator.

9. The preparation method according to claim 9, characterized in that, The firing temperature is 1500–1550℃.